FACTORS AFFECTING EDUCATIONAL AND VOCATIONAL PLANS OF FOSTER CARE CHARGES - Ruszkowska, Marzena; Matejek, Józefa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The objective of a foster care is to ensure that a child who is deprived of the adequate care from the biological family lives in the adequate environment. People who deal with Foster care responsibilities are bound to ensure a proper care to a child as well as prepare this child to future life, including vocational one. Thus, essential are educational and vocational plans of charges since they affect the process of gaining the autonomy by a youngster. The three actions: firstly, analysing the literature, secondly, doing researches in bialski poviat, thirdly, conducting a narrative questionnaire with an educator who simultaneously holds the responsibility for teaching charges autonomy, these three are supposed to identify factors that affect educational and vocational plans that foster care charges have. Factors that play significant role are as follows: a kind of foster care (family-run children houses versus educational care centres), the influence exerted by a subject and people who are supposed to support the process of gaining autonomy (foster care provider, tutor, pedagogue, educator responsible for teaching autonomy), personal characteristics (for example low self-esteem, lack of willingness and motivation to learn, lack of skills) and environmental factors (impact of dysfunctional family environment, peer environment, local environment).